High-Speed Annealing of Hydrous Ruthenium Oxide Nanoparticles by Intensely Pulsed White Light for Supercapacitors - Yoo, Tae-Hee; Kim, Sun Min; Lim, Jung Ah; Kim, Jong-Huy; Sang, Byoung-In; Song, Yong-Won (ELECTROCHEMICAL SOC INC, 2013)
We propose and demonstrate an extremely efficient annealing for the RuO2 center dot xH(2)O nanoparticles incorporated in a supercapacitor employing intensely pulsed white light (IPWL). The IPWL process ensures the significant advantage of a room-temperature and millisecond-scaled process under ambient conditions. Resultant nanomorphology and crystallinity of RuO2 center dot xH(2)O electrodes are analyzed for process optimization. Electrochemical characteristics of the IPWL-treated electrodes were investigated by cycle voltammetry, resulting in a specific capacitance of 439 F/g at 10 mV/s with the irradiated IPWL energy of 2.04 J/cm(2) in 23 msec. (C) 2013 The Electrochemical Society. All rights reserved.
Keywords: CHARGE STORAGE MECHANISM; FILM ELECTRODES; RUO2; CONDUCTIVITY; BEHAVIOR